(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the association between olfactory fossa depth according to the Keros classification, agger nasi cells, and frontal sinus opacification on computed tomography, and to analyze the combined role of these two anatomical factors in the frontal recess crowding effect. Materials and Methods: This cross-sectional analytical study was conducted on 164 sinus sides from 82 adult patients who underwent paranasal sinus computed tomography at Nhan Dan Gia Dinh Hospital from June 2024 to June 2025. Olfactory fossa depth was classified according to the Keros classification. The presence of agger nasi cells and frontal sinus opacification were recorded on computed tomography. Frontal sinus opacification was defined as a Lund-Mackay score of ≥1 for the frontal sinus. A generalized estimating equation (GEE) logistic regression model was used to adjust for the potential correlation between the two sinus sides within the same patient. Results: Keros type 2 was the most common anatomical pattern, accounting for 93.9%. The rate of frontal sinus opacification increased with olfactory fossa depth: 0.0% in Keros type 1, 22.7% in Keros type 2, and 60.0% in Keros type 3. The group with Keros type 3 combined with the presence of an agger nasi cell had the highest rate of frontal sinus opacification, reaching 75.0%. GEE analysis showed that when Keros classification was treated as an ordinal variable, a higher Keros grade was associated with an increased likelihood of frontal sinus opacification on computed tomography. Conclusion: Olfactory fossa depth is associated with frontal sinus opacification on computed tomography. The combination of Keros type 3 and the presence of an agger nasi cell suggests a possible frontal recess crowding effect, which may substantially narrow the frontal recess and impair sinus drainage. Therefore, surgeons should carefully consider adequate surgical clearance of the frontal recess in cases with high-risk anatomical features.